Association of Helicobacter pylori Infection with Type 2 Diabetic Patients in Dohuk Governorate, Iraq - Al-Rawi, Nada F.; Al-Khafaf, Abeer H.; Ibrahem, Hiyam A.; Hussein , Nawfal R. (Iraqi Journal of Science, 2022)
Helicobacter pylori (H. pylori) is one of the most common human pathogens in the world. Several studies that have investigated the correlation between H. pylori infection and type 2 diabetes mellitus (DM) found that H. pylori infection is more frequent in the patients, while the results of other studies were unclear. This paper aims to investigate the interrelation between the infection with H. pylori and type 2 DM in Dohuk governorate, Iraq. Eighty four diabetes patients (41 males, 43 females) and 92 healthy controls were involved in this study. H. pylori status was assessed in serum samples by using ELISA test. Out of the 84 patients, 65 patients (77.4%) were H. pylori positive (+ve) and 19 (22.6%) were H. pylori negative (-ve), with the difference being statistically significant. This paper found that diabetes is significantly associated with the infection of H. pylori in the studied sample of Iraqi patients.